Performance Measurement of PT. Pos Indonesia (Persero) Using Value for Money - Trivosa Aprilia Novadiani Haidiputri; Saiful Bahri; Rr. Setyani Hidayati; Ghiyasul Mustagis (Innovation Business Management and Accounting Journal, 2022)
This research was conducted at PT. Pos Indonesia (Persero) Probolinggo City. The purpose of this study was to measure the performance of PT. Pos Indonesia (Persero) Probolinggo City using value for money. This research is quantitative descriptive. The method of data collection is with documentation. The population in this study is the budget realization report of PT. Pos Indonesia (Persero) Probolinggo City, and the sample is the 2018 2019 and 2020 budget realization report. The sampling technique used is purposive sampling, with the data analysis method using descriptive statistics. The results in this study indicate that the performance of PT. Pos Indonesia (Persero) City of Probolinggo in terms of economic elements, efficiency and effectiveness have not met the requirements for value for money. This is indicated by the average value of the ratio, efficiency and effectiveness in 2018-2020 obtained results of <100% or have not met the criteria of economy, efficiency and effectiveness.